Grief and COVID-19: a narrative review in the context of pandemic - Flandes M, Gabriela; Catalán del V., Camila; Tala T., Alvaro (Revista de Psiquiatría Clínica, 2022)
Since death is inevitable, the grieving process is universal. Today, the COVID-19 pandemic has made death a daily reality and has caused a change in the way in which the medical care of patients is carried out. Many of these elements are risk factors for developing adverse grief outcomes in the bereaved. For its best approach, it is relevant to know the process normal grief and complicated grief, the general risk factors and those present in a pandemic that could lead to an adverse result, the peculiarities of the process of death and grief in the current context and the recommendations for relatives and health personnel on how to approach these processes.